2012
DOI: 10.1186/1743-7075-9-11
|View full text |Cite
|
Sign up to set email alerts
|

Diet supplementation with green tea extract epigallocatechin gallate prevents progression to glucose intolerance in db/db mice

Abstract: BackgroundGreen tea was suggested as a therapeutic agent for the treatment of diabetes more than 70 years ago, but the mechanisms behind its antidiabetic effect remains elusive. In this work, we address this issue by feeding a green tea extract (TEAVIGO™) with a high content of epigallocatechin gallate (EGCG) or the thiazolidinedione PPAR-γ agonist rosiglitazone, as positive control, to db/db mice, an animal model for diabetes.MethodsYoung (7 week-old) db/db mice were randomized and assigned to receive diets s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 33 publications
8
94
1
2
Order By: Relevance
“…Antidiabetic or lipid lowering properties of green tea or EGCG have been demonstrated in rodent models of type 2 diabetes as well as obesity (26,76,84,94). In diabetic db/db mice, EGCG increases the size and number of pancreatic islets and improves ␤-cell morphology, leading to better glucose tolerance comparable to rosiglitazone (63). Moreover, in human subjects who smoke or those with coronary artery disease, consumption of green tea significantly reverses their endothelial dysfunction (59,88).…”
Section: Examples Of Paradigmatic Studies Of Functional Foodsmentioning
confidence: 99%
“…Antidiabetic or lipid lowering properties of green tea or EGCG have been demonstrated in rodent models of type 2 diabetes as well as obesity (26,76,84,94). In diabetic db/db mice, EGCG increases the size and number of pancreatic islets and improves ␤-cell morphology, leading to better glucose tolerance comparable to rosiglitazone (63). Moreover, in human subjects who smoke or those with coronary artery disease, consumption of green tea significantly reverses their endothelial dysfunction (59,88).…”
Section: Examples Of Paradigmatic Studies Of Functional Foodsmentioning
confidence: 99%
“…In human pancreatic islets stimulated with high glucose, EGCG lowers insulin secretion along with a decrease of intracellular glutamate [23]. EGCG has been shown to reduce the body weight of obese subjects [24] and of various animal models [25,26], as well as to improve glucose tolerance in diabetic db/db mice [27]. However, the poor bioavailability of EGCG may limit its use and human trials have shown some inconsistencies [26,28].…”
Section: Preventing Obesity By the Limitation Of Insulin Secretionmentioning
confidence: 99%
“…Curcumin improved insulin resistance and glucose tolerance in type 2 diabetic db/db mice but not in nondiabetic db/+ mice (Seo et al, 2008). Green tea extract containing EGCG markedly improved glucose tolerance and increased glucose-stimulated insulin secretion by preserving islet structure in diabetic db/db (leptin receptor mutant) mice (Wolfram et al, 2006;Ortsäter et al, 2012). The natural flavonoids quercitrin, quercetin, and genistein attenuated hyperglycemia and increased insulin sensitivity in a mouse model of diabetes (Lee, 2006;Kobori et al, 2009;Babujanarthanam et al, 2010).…”
Section: Phytochemicals and Adaptive Responsesmentioning
confidence: 99%